What a waste : outsourcing and how it goes wrong /: outsourcing and how it goes wrong. (2015) - Bowman, Andrew; Ertürk, Ismail; Folkman, Peter, 1945-; Froud, Julie; Haslam, Colin; Johal, Sukhdev; Leaver, Adam; Moran, Michael, 1946-; Tsitsianis, Nick; Williams, Karel
No abstract available